Pemberdayaan Ekonomi Masyarakat Berbasis Pupuk Organik Dengan Campuran Mikroba di Desa Wayhuwi Kecamatan Jatiagung Kabupaten Lampung Selatan - Rajiman; Yulfriwini; Ikhsan Karim; Aprizal; Jhonson Limbong; Aprilia Debora C.J. (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The development of organic agriculture at this time has become one of the alternative technologies to overcome environmental problems. This research was conducted in Wayhuwi Village, Jati Agung District, South Lampung Regency. This research is a community service activity in an effort to utilize livestock manure into organic fertilizer. The method used in this research is the method of training and community empowerment. The purpose of this service is to create public awareness in processing and maintaining natural wealth. The manufacture of Organic Fertilizer (PUPOR) with this microbial mixture is fully supported by the Wayhuwi Village community. Due to their ignorance, they manage animal manure which is beneficial and causes environmental pollution so that it disturbs the comfort of the population, both in terms of health and others.Keywords: Organic Fertilizer, Animal Manure, Environmental Hygiene.